Health Informatics-Based Telecounseling Innovation in Mental Health Services - Alifa S Rahmadhina (Al Makki Health Informatics Journal, 2025)
Arjadi, R., Kusumawardhani, S. J., Purnomo, N., & Bockting, C. L. (2023). Benefits and challenges in implementing online mental health consultation in Indonesia: Survey in practitioners. Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 10(2), 284–299. DTO Kemenkes RI. (2024). Reflecting the mental health situation in Indonesia with SATUSEHAT. Medium. https://medium.com/@dtokemkes/reflecting-mental-health-situation-in-indonesia-with-satusehat Geraldina, A. M., Suen, M. W., & Suanrueang, P. (2023). Online mental health services during COVID-19 pandemic in Indonesia: Challenges from psychologist perspective. PLoS ONE, 18(6), e0285490. https://doi.org/10.1371/journal.pone.0285490 Lim, C. T., & Fuchs, C. (2024). Integrated digital mental health care: A vision for addressing population mental health needs. International Journal of General Medicine, 17, 359-365. https://doi.org/10.2147/IJGM.S449474 Munira, L., Liamputtong, P., & Viwattanakulvanid, P. (2023). Barriers and facilitators to access mental health services among people with mental disorders in Indonesia: A qualitative study. Belitung Nursing Journal, 9(2), 110-117. https://doi.org/10.33546/bnj.2521 Ospina-Pinillos, L., et al. (2025). Co-designing, developing, and testing a mental health platform for young people using a participatory design methodology in Colombia: Mixed methods study. JMIR Human Factors, 12(1), e66558. https://doi.org/10.2196/66558 Saptandari, E. W. (2020). Covid-19 and mental health: The growing need of telecounseling in Indonesia. Buletin Psikologi, 28(2), 99-112. https://doi.org/10.22146/buletinpsikologi.59542 Thakkar, A., Gupta, A., & De Sousa, A. (2024). Artificial intelligence in positive mental health: A narrative review. Frontiers in Digital Health, 6, 1280235. https://doi.org/10.3389/fdgth.2024.1280235 Torous, J., Linardon, J., Goldberg, S. B., et al. (2025). The evolving field of digital mental health: Current evidence and implementation issues for smartphone apps, generative artificial intelligence, and virtual reality. World Psychiatry, 24(2), 156-174. https://doi.org/10.1002/wps.21299 Braun, V., & Clarke, V. (2006). Using thematic analysis in psychology. Qualitative Research in Psychology, 3(2), 77-101. Creswell, J. W., & Clark, V. L. P. (2018). Designing and conducting mixed methods research (3rd ed.). Sage Publications. Moran, N., & O'Brien, N. (2022). System Usability Scale benchmarking for digital health apps: Meta-analysis. JMIR mHealth and uHealth, 10(8), e37290. Skivington, K., Matthews, L., Simpson, S. A., et al. (2021). A new framework for developing and evaluating complex interventions: Update of Medical Research Council guidance. BMJ, 374, n2061. Sousa, V. D., & Rojjanasrirat, W. (2011). Translation, adaptation and validation of instruments or scales for use in cross-cultural health care research. Journal of Evaluation in Clinical Practice, 17(2), 268-274. Bangor, A., Kortum, P., & Miller, J. (2009). Determining what individual SUS scores mean: Adding an adjective rating scale. Journal of Usability Studies, 4(3), 114-123. Berardi, C., Hine, M., Bélanger, F., & Bhatikar, S. (2024). Barriers and facilitators to the implementation of digital technologies in mental healthcare systems: A qualitative systematic review. BMC Health Services Research, 24, 243. Chen, Y., Wang, L., & Zhang, H. (2024). Effectiveness of telemedicine on common mental disorders: An umbrella review and meta-meta-analysis. Computers in Human Behavior, 157, 108236. Cuijpers, P., Karyotaki, E., de Wit, L., & Ebert, D. D. (2019). The effects of fifteen evidence-supported therapies for adult depression: A meta-analytic review. Psychotherapy Research, 30(3), 279-293. DTO Kemenkes RI. (2024). Reflecting mental health situation in Indonesia with SATUSEHAT. Medium. https://medium.com/@dtokemkes Fischer-Grote, L., Fössing, V., Aigner, M., Fehrmann, E., & Boeckle, M. (2024). Effectiveness of online and remote interventions for mental health in children, adolescents, and young adults after the onset of the COVID-19 pandemic: Systematic review and meta-analysis. JMIR Mental Health, 11, e46637. Greenwood, H., Krzyzaniak, N., Peiris, R., et al. (2022). Telehealth versus face-to-face psychotherapy for less common mental health conditions: Systematic review and meta-analysis of randomized controlled trials. JMIR Mental Health, 9(3), e31780. He, Y., Chen, J., & Wang, X. (2023). Systematic review and meta-analysis of AI-based conversational agents for promoting mental health and well-being. npj Digital Medicine, 6, 236. Lewis, C. C., Boyd, M., Puspitasari, A., et al. (2019). Implementing measurement-based care in behavioral health: A review. JAMA Psychiatry, 76(3), 324-335. Linardon, J., & Fuller-Tyszkiewicz, M. (2020). Attrition and adherence in smartphone-delivered interventions for mental health problems: A systematic and meta-analytic review. Journal of Consulting and Clinical Psychology, 88(1), 1-13. Moran, N., & O'Brien, N. (2022). System Usability Scale benchmarking for digital health apps: Meta-analysis. JMIR mHealth and uHealth, 10(8), e37290. Munira, L., Liamputtong, P., & Viwattanakulvanid, P. (2023). Barriers and facilitators to access mental health services among people with mental disorders in Indonesia: A qualitative study. Belitung Nursing Journal, 9(2), 110-117. Ospina-Pinillos, L., Shambo-Rodríguez, D. L., Sánchez-Nítola, M. N., et al. (2025). Co-designing, developing, and testing a mental health platform for young people using a participatory design methodology in Colombia: Mixed methods study. JMIR Human Factors, 12(1), e66558. Patel, V., Saxena, S., Lund, C., et al. (2018). The Lancet Commission on global mental health and sustainable development. The Lancet, 392(10157), 1553-1598. Rutter, T. L., Saris, I. M., Loeffen, C., et al. (2024). The association between quality of therapeutic alliance and treatment outcomes in teletherapy: A systematic review and meta-analysis. Clinical Psychology Review, 110, 102426. Simpson, S. G., Reid, C. L., & Richardson, L. K. (2019). Videoconference-based psychotherapy: A review of the literature. In J. Practical Telehealth (Eds.), Telemental Health (pp. 45-68). Springer. Simpson, S., Richardson, L., Pietrabissa, G., Castelnuovo, G., & Reid, C. (2021). Videotherapy and therapeutic alliance in the age of COVID-19. Clinical Psychology & Psychotherapy, 28(2), 409-421. Torous, J., Linardon, J., Goldberg, S. B., et al. (2025). The evolving field of digital mental health: Current evidence and implementation issues for smartphone apps, generative artificial intelligence, and virtual reality. World Psychiatry, 24(2), 156-174. Välimäki, M., Anttila, K., Anttila, M., & Lahti, M. (2023). Factors affecting digital tool use in client interaction according to mental health professionals: Interview study. JMIR Human Factors, 10, e44681. Wani, C., McCann, L., Lennon, M., & Radu, C. (2024). Digital mental health interventions for adolescents in low- and middle-income countries: Scoping review. Journal of Medical Internet Research, 26, e51376. World Health Organization. (2024). Ethics and governance of artificial intelligence for health: Guidance on large multi-modal models. WHO. Yew, S. Q., Trivedi, D., Adanan, N. I. H., & Chew, B. H. (2025). Facilitators and barriers to the implementation of digital health technologies in hospital settings in lower- and middle-income countries since the onset of the COVID-19 pandemic: Scoping review. Journal of Medical Internet Research, 27(1), e63482. Zayed, M., Ibrahim, A., & Hassan, M. (2024). Acceptability of tele-mental health services among users: A systematic review and meta-analysis. BMC Public Health, 24, 1012.